Characterization of Activated Carbon-Waste Tyre Char by CO2 Activation from Calcium Carbonate - Thanga Raj, Joanna Ruth (Universiti Teknologi PETRONAS, 2016)
The focal point of this research is to study the characteristics of activated carbon synthesized from pyrolysis of waste tyre char and calcination of calcium carbonate at elevated temperature. In this experiment, waste tyre char undergone thermo chemical decomposition using a fixed bed drop type pyrolyzer at 350℃ that produced pyrolytic oil, non-condensable gas and tyre char. Tyre char from pyrolysis and calcium carbonate were placed in an activator with temperature determined from Thermogravimeric Analysis (TGA). Calcium carbonate breaks into calcium oxide and carbon dioxide during this high temperature so the carbon dioxide will activate the char to produce activated carbon. Waste tyre char was activated by physical activation for 800℃, 850℃ and 900℃ and the duration of activation is from 1 hour to 3 hours. Scanning Electron Microscopy (SEM) was used to analyze the morphology structure while Fourier Transformation Infrared (FTIR) was used to study the functional group present in the waste tyre char and activated carbons.